Short Communication: Further morphological evidence for separating Mukia Arn. from Cucumis L. - MENTARI PUTRI PRATAMI; TATIK CHIKMAWATI; RUGAYAH RUGAYAH (Society for Indonesian Biodiversity, 2019)
Pratami, MP Chikmawati T, Rugayah. 2019. Short Communication: Further morphological evidence for separating Mukia Arn. from Cucumis L.. Biodiversitas 20: 211-217. Mukia Arn. is closely related to Cucumis L. based on molecular data, nevertheless, they have high morphological differences resulting in different opinion on taxonomical status of the two genera. Mukia Arn. has many similarities in pollen and leaf anatomical characters to Cucumis L., but both genera differ in seven seed characters, i.e color, shape, size, surface pattern, seed edge, transverse section at seed neck, and the markings of the inner seed coat surface. So, based on seed characteristics, Mukia Arn. is separated from Cucumis L.Keywords: Cucurbitaceae, leaf anatomy, Malesia